RELEVANCE OF BIO IMPEDANCE SPECTROSCOPY FOR THE ESTIMATION OF BODY COMPOSITION IN DIALYSED AND KIDNEY TRANSPLANTED PATIENTS - Karine Moreau; Aurélie Desseix; Nicole Barthe; Philippe Chauveau (The Korean Society of Nephrology, 2012)
Bio impedance spectroscopy (BIS) is widely used in pathological situations to measure body composition. However, the results of BIS validation with reference methods are still contradictory, especially in medical situations where hydratation status is compromised. The aim of this study was to evaluate the accuracy of BIS to estimate fat free mass (FFM) and fat mass (FM) in dialysed patients using dual-energy X-ray absorptiometry (DXA) as a reference compared to the results obtained in the same patients two years after successful kidney transplantation. When listed for a kidney grafting, 39 patients who consent were included in a longitudinal study of evaluation of body composition (CORPOS). FFM and FM were estimated by DXA and by BIS (Imp SFB7 Impedimed Pty Ltd. Queensland, Australia), both performed successively the same day. These measurements were repeated in the same patients 24 months after renal transplantation. DXA and BIS measures of FFM and FM were highly correlated in dialyzed patients (DP) (respectively r=0.909 p<0.001 and r=0.831 p<0.001) and kidney transplant recipients (KTR) (respectively r=0.934 p<0.001 and r=0.770 p<0.001). The mean difference between DXA and BIS (Bland-Altman analysis) for FFM estimation was smaller in KTR (-0.3 +/- 4.9 vs 3.2 +/- 4.5 in DP), whereas difference did not reach significance for FM. Differences between upper and lower limits are important in all groups: -5 to 15.5kg for FFM in DP; -10.2 to 8.8kg for FFM in KTR; -11.6 to 6.8kg for FM in DP and -9 to 14.9kg for FM in KTR. Despite this individual variability, the whole body composition evolution after kidney transplantation is approached the same way by both methods. DXA and BIS measurements were highly correlated in both DP and KTR. However, the large individual differences demonstrated that single values of FFM or FM may be interpreted carefully but BIS as DXA has ability to evaluate changes in body composition over time in longitudinal studies.